Investigation of the ability of final-year medical students to deliver bad news - Seyedpouya Paknezhad; Zahra Vand Rajabpour (Journal of Research in Clinical Medicine, 2023)
Introduction: Delivering bad news (DBN) is an essential communication for all doctors. There are many benefits of DBN, for both the patient and the healthcare team looking after the patient. Having a general perspective of the ability of medical students in DBN can help us to improve educational programs in the future; therefore, the purpose of this study was to investigate the ability of final-year medical students to DBN. Methods: 150 final-year medical students, who were undergoing their internship in different clinical courses, participated in this study. The translated questionnaire of SPIKES guidelines was used to measure the skill of senior medical students in DBN to patients, which includes 16 questions. Student t-test was used to compare quantitative variables and a chi-square test was used to compare qualitative variables. Results: The mean age of participants was 26.19±.94 years with a minimum age of 26 years with a median of 29 years. (36%0) males and 96(64%) females formed the study population. the total score and the environmental score of DBN are significantly higher in female students. Also, according to the Pearson test, no significant correlation was observed between the age of the final year and the fields of ability in DBN (P=0.512, r=0.021). Conclusion: Due to the lack of sufficient training on how to communicate with patients and deliver bad news, adding a training program to increase the skills of medical students in DBN to the general medical training curriculum can be useful in improving the academic aspects of general practitioners.